2005
DOI: 10.1108/07363760510631110
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐to‐consumer advertising and young consumers: building brand value

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…DTCA and Young Adults 233 Baca, Holguin, and Stratemeyer (2005) considered the issue of prescription drug advertising and youth ''perplexing,'' because such advertising is generally directed toward older consumers, but they cite two phenomena that suggest a shift in the trend (p. 380). First, they claimed some medications, such as those directed toward allergy sufferers are advertised to a ''broad age group,'' and second, they cite the growing number of younger people who care for older people that are inadvertently consuming prescription drug advertising.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…DTCA and Young Adults 233 Baca, Holguin, and Stratemeyer (2005) considered the issue of prescription drug advertising and youth ''perplexing,'' because such advertising is generally directed toward older consumers, but they cite two phenomena that suggest a shift in the trend (p. 380). First, they claimed some medications, such as those directed toward allergy sufferers are advertised to a ''broad age group,'' and second, they cite the growing number of younger people who care for older people that are inadvertently consuming prescription drug advertising.…”
mentioning
confidence: 97%
“…While the pharmaceutical industry has agreed not to market medications to those under 18 years old, the present study is concerned about the direction of those marketing efforts, the degree to which the industry is reaching younger consumers in terms of awareness and knowledge, and the impact such advertising may have on their attitudes toward DTC prescription drug advertising, including how those attitudes may impact their broader view of the casual use of pharmaceuticals in general. During the pre-social-media era, young adults (below the age of 25) demonstrated awareness and interest in prescription drug advertising, but perhaps because of their general good health they were not moved toward interest or action regarding prescription drugs (Baca et al, 2005). In fact, Frank, Berndt, Donohue, Epstein, and Rosenthal (2002) reported that over 90% of consumers have seen a prescription drug advertisement.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, less is known about the appropriate use of prescription drugs among college age adults and how this group is influenced by DTCA. In one study among the limited research pertaining to this topic, Baca et al (2005) applied a hierarchy of effects model to examine the effects of DTCA on young adults. Findings indicated the sample of undergraduate college students had relatively high interest and neutral attitudes toward DTCA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This presents a unique marketing potential for pharmaceutical companies. Furthermore, DTCA can contribute to developing brand equity among young consumers (Baca, Holguin, & Stratemeyer, 2005;Kadison, 2005).…”
mentioning
confidence: 99%